Tangled relationships : managing boundary issues in the human services - Reamer, Frederic G., 1953- (Columbia University Press, 2001)
Reamer examines the ethics involving intimate and sexual relationships with clients and former clients, practitioners' self-disclosure, giving and receiving favors and gifts, bartering for services, and unavoidable and unanticipated circumstances such as social encounters and geographical proximity. Case vignettes help illustrate important points. Reamer also gives practical risk-management models to aid human service professionals in the prevention of problematic situations and the managing of dual relationships.
Keywords: Social workers -- Professional relationships.; Human services personnel -- Professional relationships.; Counselor and client.; Social service.; Social Work; Travailleurs sociaux -- Relations professionnelles.; Services sociaux -- Personnel -- Relations professionnelles.; Relations conseiller-client.; Service social.; SOCIAL SCIENCE -- Social Work.; Counselor and client; Social service; Social ethics & debates.; Social issues & welfare.